RESPON PERTUMBUHAN SEMAI MERANTI TEMBAGA (Shorea leprosula Miq.) PADA MEDIUM CAMPURAN TOPSOIL DANKOMPOS DENGAN BERBAGAI TINGKAT NAUNGAN - Setiawan, Agus; Sribudiani, Evi; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Shorealeprosula included major timber producing tree and widely used include the use of such, plywood, sawn timber, and buildings of contruction.Shorealeprosulaproductiondecreasedamount, becausemost of the production comes fromnatural forests. The cultivation needed so shorealeprosula not become extinct, for it is important in the provision of quality seedlings. Shorealeprosula includedsemi tolerant types that require low light intensity for early growth. The nursery needed microclimate modification that environment conditionaccording to the requirement growing seedlings shorealeprosula.Alternativemade is bygivingshadeinthe nurseryShorealeprosula. This research aimstodetermine the effect ofshadeon the successandthe intensity ofthe shadeis best, on the growth ofseedlingsShorealeprosula the medium topsoil and compost mixture ratio 1:1.This research uses a completely randomize design method which consist of 5 treatments, 3 replications, and 5 units of the plant as a research unit.P0 = Without giving shade; P1 = the provision of shade level of 45%; P2 = the provision of shade level of 60%; P3 = the provision of shade level of 90%. The result indicates that treatment giving shade level of 90% is the best treatment on the parameters of observation, the high increasing (2,24 cm), the diameter increasing (1,2 mm) for seedlings Shorealeprosula in medium topsoil and compost mixture ratio 1:1. Keyword: Growth, seedling shorealeprosula, shade.